Effect of low dose Methotrexate in newly diagnosed Rheumatoid arthritis case (Bangladesh Critical Care Journal, 2021)
Rheumatoid arthritis is a painful debilitating joint disease with the proliferation of the synovium and progressive erosion of cartilage and bone. Methotrexate (MTX) has been used for the treatment of Rheumatoid Arthritis (RA) for about 3 decades. It is most effective and commonly used Disease Modifying Antirheumatic Drugs (DMARDS) because it improves symptoms, signs, disease activity and functions. This study was done from January 2016 to December 2016 for a period of 1 year under Physical Medicine and Rehabilitation department, Jalalabad Ragib-Rabeya Medical College (JRRMC), Sylhet. Here we treated the patients with low dose methotrexate. Study was done to see the effect of low dose MTX in newly diagnosed RA patients by clinical examination and DAS 28. DAS stands for disease activity score and 28 joints that are examined in this assessment. The result concluded low dose MTX improves the symptoms, signs, disease activity and functions of the patients.Bangladesh Crit Care J March 2021; 9(1): 34-37